Integrated precision nutrient management approach - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Integrated nutrient management approaches were developed, tested and evaluated in collaboration with key stakeholders. . Several capacity development and engagement campaigns were organized and now federal and various state governments of India are adopting this approach to improve nutrient-use-efficiency, increase yield and income and reduced environmental footprint as byproduct.